Optimasi Penggunaan Koagulan PC300 dan Flokulan A100 untuk Proses Pengolahan Air Limbah Tambang di WWTP01 PT. Mitrabara Adiperdana,Tbk - Riyadil Afdal; Fadhilah Fadhilah (Departemen Teknik Pertambangan FT UNP, 2020)
Abstract. PT. Mitrabara Adiperdana, Tbk is a company engaged in coal mining which was established in Kec. South Malinau in Kab. Malinau Province of North Kalimantan. To support coal production activities, PT. Mitrabara Adiperdana, Tbk has to pump the water in the sump and then process it to be released into the river. During the first semester of 2018, the average air processed by PT. MItrabara Adiperdana, Tbk in WWTP01 is 1,600,000 m3/month. The dose of coagulant use is 173 ppm and flocculant 44 ppm to produce outlets 130-140 mg / l. After optimizing the dosage, an optimal dosage is obtained, namely 160 ppm coagulant dose and 40 pm flocculant dose to produce final tss 190 mg / l, still included in the Environmental Quality Standards. After that the dose optimization is done, the chemical needs of PT. Mitrabara Adiperdana, Tbk in each month is 256,000 kg of coagulant and 64,000 kg of flocculant.Keywords: Waste Water Treatment,Optimasi, Koagulasi, Flokulasi, Total suspendi solid